KLASIFIKASI OPINI MASYARAKAT TENTANG HARGA KARET MENGGUNAKAN MACHINE LEARNING - Yustida Bellini; M Izman Herdiansyah; Tri Basuki Kurniawan; Yesi Novaria Kunang (Jusikom : Jurnal Sistem Komputer Musirawas, 2023)
Indonesia is the world’s largest rubber producer after Thailand with an average income of 3.107.544 tons/year, with these data many Indonesian people become rubber farmers to make ends meet. The price of rubber has a large impact on the lives of the Indonesian people so that when the price of tubber decreases or increases, many people speculate and have opinions about the price of rubber, therefore this study aims to classify public opinion regarding the price of rubber. People’s opinions and expressions regarding the price of rubber are often expressed by them on the social networking site Twitter, Twitter is the most common public means of expressing the emotions of people all over the world today. In this study, the classification of public opinion regarding rubber prices was carried out based on public opinion on the social networking site Twitter. The purpose of this study is to find out the sentiments circulating on Twitter regarding the price of rubber using Naïve Bayes algorithm. Based on the result of the research that has been done, negative sentiment is obtained by 92% and positive sentiment is obtained by 62%, while the accuracy value is obtained by 84%. The conclusion of this study is that the community has more negative than positive opinions about the price of rubber.